Nuclear β‐catenin and CDX2 expression in ovarian endometrioid carcinoma identify patients with favourable outcome. Issue 3 (15th January 2019) - Wang, Linyuan; Rambau, Peter F; Kelemen, Linda E; Anglesio, Michael S; Leung, Samuel; Talhouk, Aline; Köbel, Martin
Abstract : Aims: Ovarian endometrioid carcinoma (EC) generally has a good prognosis. Adjuvant chemotherapy can be spared in low‐stage disease, but prognostic biomarkers are needed to refine the treatment threshold. Wnt/β‐catenin signalling is commonly altered in EC. We examined immunohistochemical expression of nuclear β‐catenin and CDX2 as prognostic biomarkers for EC; both are mediators of the Wnt pathway. Methods and results: We evaluated two ovarian EC cohorts, discovery set ( n  = 183) and validation set ( n  = 174), with ovarian cancer‐specific survival (OCSS) as the primary end‐point. In univariable analysis, nuclear β‐catenin expression was significantly associated with longer OCSS in the discovery set [hazard ratio (HR) = 0.36, 95% confidence interval (CI) = 0.16–0.74, P  = 0.004] and the validation set (HR = 0.35, 95% CI = 0.11–0.89, P  = 0.006). Similar significant associations were observed with CDX2 expression in the discovery set (HR = 0.25, 95% CI = 0.11–0.50, P  < 0.001) and validation set (HR = 0.27, 95% CI = 0.07–0.75, P  = 0.020). In multivariable analysis, combined positivity of both markers was significantly associated with longer OCSS in the discovery set (HR = 0.20, 95% CI = 0.06–0.49, P  < 0.001) and in the validation set (HR = 0.33 95% CI = 0.07–0.1.06, P  = 0.047). In a stratified analysis for stage IC/II EC, combined positivity identified a subset of patients with a significantly longer OCSS in the discovery cohort but only a non‐significant trend in the validation cohort. Conclusions: Nuclear β‐catenin and CDX2 expression individually or in combination are validated prognostic markers for ovarian EC. However, their full potential to stratify low risk patients at adjuvant threshold awaits further multimarker study.